CO2 Reforming of CH4 Over Ni/SBA-15 Prepared by Surfactant-Assisted Impregnation Method: Comparative Study of Surfactant Types - C. C., Chong; A. H. K., Owgi; N. Aini, Razali; Chin, S. Y.; Setiabudi, H. D. (2017)

(untitled)
This research focused on the influence of surfactant types of surfactant-assisted impregnation method on the properties and catalytic activity of Ni/SBA-15 towards CO2 reforming of CH4(CRM). Three types of surfactant were used which are nonionic surfactant (poly(ethylene glycol)-poly(propylene glycol)-poly(ethylene glycol), P123), cationic surfactant (cethyltrimethylammonium bromide, CTAB) and anionic surfactant (sodium dodecyl sulfate, SDS) to synthesize Ni/SBA-15(P123), Ni/SBA-15(CTAB) and Ni/SBA-15(SDS), respectively. The synthesized catalysts were characterized using X-ray Diffractometer (XRD), Brunauer-Emmett-Teller (BET) and Fourier-Transform Infrared (FTIR) to study the physical and chemical properties of synthesized catalysts. The CRM was carried out in a stainless steel fixed bed reactor at 800°C and CO2/CH4 ratio = 1/1. The obtained results indicated that the types of surfactant greatly influence the properties and catalytic activity of Ni/SBA-15. The activity of catalysts followed the order of SBA-15 < Ni/SBA-15(SDS) < Ni/SBA-15(CTAB) < Ni/SBA-15 < Ni/SBA-15(P123) with the conversion of CH4 and CO2 over Ni/SBA- 15(P123) were about 92% and 82%, respectively and H2/CO ratio of 1.22. The superior catalytic performance of Ni/SBA-15(P123) might be related with the well dispersion of Ni particles which enhanced the stabilization of the active metal sites on SBA-15 and ameliorated the properties of catalyst towards an excellent catalytic performance. This study provides a new perspective on the preparation of Ni/SBA-15, particularly in the influence of surfactant types of surfactant-assisted impregnation method towards an excellent CRM.